Willingness to pay a price premium for certified wood products among consumers in Malaysia - Mohamed, Shukri; Abd. Ghani, Awang Noor (Universiti Putra Malaysia Press, 2010)
Consumers are assumed to be willing to pay price premiums for certified wood products. In this study, Malaysian consumers’ willingness to pay a price premium for certified wood products and factors influencing their willingness to pay were investigated. The study made use of the data obtained from 994 systematically selected mall-intercepted respondents. A binomial logit analysis was applied to determine the factors influencing the respondents’ willingness to pay. About 74% of the respondents indicated that they would choose wood products made from certified timbers. However, only 57% stated that they were willing to pay a price premium for the products. The respondents’ willingness to pay was found to be influenced by their knowledge and perceived importance of forest certification, as well as the inclination to choose wood products made from certified timbers. There is also a positive correlation between the willingness to pay and the respondents’ education, income, and current ownership of the wooden furniture items. The opportunity for further research includes determining the amount of premium the consumers are willing to pay and identifying consumer segments where certified wood products can be successfully marketed.